2009
DOI: 10.1097/01.nmc.0000347306.15950.ae
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Labor Friends Initiative

Abstract: The provision of culturally appropriate social support is critical in the care of Hispanic immigrant childbearing women. Programs such as the Hispanic Labor Friends Initiative can help improve support and promote positive outcomes in these vulnerable and disadvantaged women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Hazard [ 68 ] interviewed Spanish-speaking Hispanic women to evaluate a culturally-sensitive program of labor support compared to women who received standard care. Women who received the intervention appreciated having the cultural and social support from trained Hispanic doulas, demonstrated increased use of healthcare resources, reported enhanced quality of informed consent, and fewer language barriers with providers.…”
Section: Resultsmentioning
confidence: 99%
“…Hazard [ 68 ] interviewed Spanish-speaking Hispanic women to evaluate a culturally-sensitive program of labor support compared to women who received standard care. Women who received the intervention appreciated having the cultural and social support from trained Hispanic doulas, demonstrated increased use of healthcare resources, reported enhanced quality of informed consent, and fewer language barriers with providers.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of implementing brief maternal screenings for PPD during well‐child and postpartum visits is well‐documented (Freeman et al, 2005; Le et al, 2009; Olson, Dietrich, Prazar, & Hurley, 2006). This may be an important strategy because many Hispanic women do not return for their postpartum maternal checkups (Hazard et al, 2009). Given the high rates consistently found among similar studies, as well as the vulnerability of this population, we strongly recommend healthcare providers including nurses implement universal screening with the PDSS‐Spanish version for all Spanish‐speaking Hispanic women across the childbearing year.…”
Section: Discussionmentioning
confidence: 99%
“…The content for these items was formulated from the comments and experiences of postpartum women during extensive qualitative study (Le, Perry, & Ortiz, 2009). The English and Spanish versions of this tool have been widely used to evaluate PPD risk among Hispanic women (Beck, Froman, & Bernal, 2003; Hazard et al, 2009; Wei et al, 2008). The authors of the PDSS‐Spanish version conducted two studies to evaluate the psychometric properties of the Spanish scale; both demonstrated an alpha internal consistency reliability of .95 for the total score, and .94 and .95 for Mexican–American women (Beck et al, 2003; Beck & Gable, 2005b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large sub-category comprises 14 interventions in which people who share cultural characteristics with a target service user group are employed to bridge the cultural gap between this group and service providers ( Table 4 ) [53] – [66] . They may fulfil various roles including encouraging and helping women to access care [57] , [59] ; assisting women in communicating with healthcare providers [55] , [56] ; and advocating on their behalf [62] . They are sometimes referred to as ‘linkworkers,’ ‘peer health workers’ or ‘cultural brokers’.…”
Section: Resultsmentioning
confidence: 99%